Acceptance and knowledge of COVID-19 vaccine in southern Kerala during first vaccination drive - Raju, Christin V.; Joseph, Hannah; Roy, Layana; Mathew, Seara M.; S., Jayakumar K.; James, Roshiny Thankam (International Journal Of Community Medicine And Public Health, 2022)
Background: Coronavirus disease 2019 (COVID-19) pandemic has affected most the countries causing a devastating influence on world health and economics since its appearance. The accelerated development of the COVID-19 vaccine has become vital, and early data suggests that it is both, safe and efficacious. However, the acceptance of the COVID-19 vaccine depends on several socio-demographic characteristics as well as people’s knowledge and misconceptions. Methods: The objective of this study was to assess the knowledge and acceptance of the COVID-19 vaccine in the southern districts of Kerala during the first vaccination drive. This is a cross-sectional study conducted by analyzing the data collected through a self-administered questionnaire that was shared online and directly across southern Kerala from January 2021 to June 2021. The survey questionnaire consisted of demographic characteristics of the respondents and queries pertaining to knowledge and acceptance of the COVID-19 vaccine. Results: The results of the study showed that the respondents showed a good level of knowledge and acceptance. This study highlights that 83.6% of the participants in South Kerala have demonstrated their willingness to receive the COVID-19 vaccine. Conclusions: Findings from this study could help governments, public health agencies, and awareness-raising organizations to address immunization hesitation and improve uptake of COVID-19 vaccines.